Hidden Mathematics in Crafting Wayang Kulit: Geometry, Proportion, and Symmetry in the Traditional Javanese Shadow Puppets - Muhammad Noor Kholid; Aisyara Zalzabila Sapruddin (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Mathematics learning is often presented in abstract forms, detached from students’ cultural experiences. This makes it difficult for learners to relate mathematical concepts with their real-life contexts. Integrating cultural artifacts into mathematics education can provide meaningful and contextual learning experiences. This study aims to explore mathematical concepts embedded in the traditional Javanese art of wayang kulit or shadow puppetry, particularly those related to geometry, proportion, and symmetry, and to examine how these concepts reveal implicit mathematical reasoning and proportional systems employed by craftsmen, and how these can be developed into a culturally grounded framework for mathematics learning. The research employed an ethnographic approach within the framework of ethnomathematics. Data were collected through semi-structured interviews, participatory observations, and documentation involving three experienced wayang kulit craftsmen in Surakarta, Indonesia. The data were analyzed using qualitative content analysis, including data reduction, categorization, and interpretation. The findings reveal that the process of crafting wayang kulit involves various mathematical ideas, including geometric shapes, proportional body structures, repeating patterns, and symmetrical ornament designs. These concepts are intuitively applied by craftsmen, drawing on accumulated experience and culturally transmitted design conventions that function as implicit mathematical rules, during the design and production process. The study highlights that wayang kulit contains meaningful geometric structures, particularly in relation to shae, proportion, and symmetry, which can serve as contextual learning resources. Therefore, integrating cultural heritage such as wayang kulit into mathematics instruction can enhance students’ conceptual understanding of geometry, particularly in shape, proportion, and symmetry, while informing the design of ethnomathematics-based instructional materials.